Synthesis of Resveratrol Loaded Hybrid Silica-PAMAM Dendrimer Nanoparticles With Emphases on Inducible Nitric Oxide Synthase and Cytotoxicity - Kececiler-Emir, Ceren; Ilhan-Ayisigi, Esra; Celen-Erden, Cigdem; Nalbantsoy, Ayse; Yesil-Celiktas, Ozlem (SPRINGER, 2021)
Resveratrol is a naturally occurring polyphenolic compound exhibiting therapeutic activities. However, the stability can be altered by UV light, pH and changes in temperature. Encapsulation would be an ideal strategy to improve the stability and bioavailability. Thus, trans-resveratrol (Res) was encapsulated within hybrid nanoparticles consisted with silica and G4 polyamidoamine dendrimer (PAMAM) by sol-gel method. The diameters of synthesized nanoparticles (NPs) were at a range of 212-574 nm and the encapsulation efficiency was 86 %. RAW 264.7 murine macrophage cell line induced with endotoxin/lipopolysaccharide was treated with free resveratrol and Res-loaded NPs for assessing inhibition of inducible nitric oxide synthase (iNOS), where IC50 values of free resveratrol and Res-loaded NPs were 122.68 mu M and 249.74 mu M. As for cytotoxicity, IC50 values of free resveratrol were found as 176.57 mu M and 201.54 mu M for MCF-7 and MDA-MB-231 cells, whereas 197.16 mu M and 219.07 mu M for Res-loaded NPs for the respective cell lines. Overall, sol-gel technique proved to be an ideal technology as can be carried out under mild conditions and Res-loaded NPs have potential to be utilized in the industry.
Keywords: Sol‐ gel; Nanoparticle; PAMAM; Resveratrol; Cytotoxicity; iNOS; Plant Sciences; Chemistry; Food Science & Technology; Nutrition & Dietetics